2020
DOI: 10.3390/ijerph17041342
|View full text |Cite
|
Sign up to set email alerts
|

Problem Gambling in the Fitness World—A General Population Web Survey

Abstract: The world of sports has a complex association to problem gambling, and the sparse research examining problem gambling in athletes has suggested an increased prevalence and particularly high male predominance. The present study aimed to study frequency and correlates of problem gambling in populations with moderate to high involvement in fitness or physical exercise. This is a self-selective online survey focusing on addictive behaviors in physical exercise distributed by ‘fitness influencers’ on social media a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 49 publications
2
7
0
Order By: Relevance
“…Our findings on the association between alcohol consumption and exercise are also consistent with previous studies [83][84][85]. However, our finding that frequent gambling does not have a significant relationship with exercise is inconsistent with Håkansson et al [86], who found a positive association between problem gambling and physical activity. Among the behavioral variables, our finding on the positive association of happiness level with regular exercise is consistent with other studies [87][88][89][90].…”
Section: Discussionsupporting
confidence: 87%
“…Our findings on the association between alcohol consumption and exercise are also consistent with previous studies [83][84][85]. However, our finding that frequent gambling does not have a significant relationship with exercise is inconsistent with Håkansson et al [86], who found a positive association between problem gambling and physical activity. Among the behavioral variables, our finding on the positive association of happiness level with regular exercise is consistent with other studies [87][88][89][90].…”
Section: Discussionsupporting
confidence: 87%
“…Problem gambling traditionally has been more common in men in the general population, but gender differences in prevalence may have become narrower during the past few years [39,40]. However, males appear to be even more over-represented with respect to problem gambling in elite athletes [19,20] and in fitness-involved young adults and adolescents [48]. In the present study, as in previous studies in athletes, problem gambling was clearly more common in men and more common in this group than likely would be the case in the general population [21,39], whereas gambling on a moderate-risk or problem level was even non-existing in women.…”
Section: Discussionmentioning
confidence: 99%
“…There may be several explanations for the markedly large gender difference in problem gambling in athletes. Although in one study only, a similar finding regarding a surprisingly large gender difference in the prevalence of problem gambling was seen from a web survey addressing people with an assumingly high interest in sports, that is, individuals with regular exercise habits and who were social media followers of well-known fitness profiles (Håkansson et al, 2020a ). First, one possible explanation may be the fact that women tend to develop gambling problems at a later age than men, such that the assessment of elite athletes, typically young adults, may not detect women who may or may not develop problem gambling later in life, but who have not yet initiated gambling patterns of the same intensity as men.…”
Section: Discussionmentioning
confidence: 62%
“…The specific effects of the COVID-19 pandemic on gambling behaviors are beyond the scope of the present review paper, but both studies clearly demonstrated a gender difference in gambling problems, as in a number of other papers here. In addition, the Swedish study, carried out with a methodology similar to a general population study in the same setting (Håkansson, 2020 ), concluded that the self-reported changes in gambling behaviors during the pandemic were similar to those reported in the general population, that is, with a limited proportion reporting an increase in gambling, but with a significant link between this and gambling problems (Håkansson et al, 2020a ). Given the extensive consequences of the pandemic on the world of sports, including career uncertainty and mental distress (Håkansson et al, 2020b ), problem gambling within the group of elite athletes may require further research attention, also with respect to the impact of COVID-19.…”
Section: Discussionmentioning
confidence: 96%